Business Process Redesign and Automation for Apotek Semoga Jaya (The Indonesian Journal of Business Administration, 2022)
Abstract, Information system implementation gives advantages to business activities in a company. SMEs to large scale businesses are competing to implement an information system in their business. Information system implementation in a business can increase the benefit from data management and information flow in their operational activities. Apotek Semoga Jaya or known as ASJ is one of the pharmacies in Padang City which still implement a manual approach for their activities. This condition makes ASJ get a problem with warehouse management. Undetected medicine stock-out makes ASJ have potential lost sales by more than one billion rupiahs in a year. Root cause analysis is implemented to get the initial cause of the ASJ’s problem. From the root cause analysis, there is no specific regulation to prevent unrecorded transactions in ASJ. Implementation of an information system comes as the solution for the ASJ’s problem. Implementation of an information system needs to consider the people, process, and technology (PPT) aspects in ASJ. The business process redesign heuristic is implemented to improve the business process on ASJ which involves PPT aspects. The implementation of the solution will be using the PDCA cycle to monitor the effectiveness of the solutions in ASJ.Keywords: Information systems, root cause analysis, business process redesign heuristic, PPT aspect, PDCA cycle.